The influence of multivitamins on neurological and growth disorders: a cross-sectional study - Zhu, Jiaxiao; Xu, Penghong; Yan, Wu; Hu, Yahui; Guo, Hongli; Chen, Feng; Bigambo, Francis Manyori; Wang, Xu (Frontiers in Nutrition, 2024)
Background: While vitamin deficiencies can pose serious health consequences for the body, excessive intake of vitamins can also lead to health risks. However, there is limited data about the impact of multivitamins on neurological and growth disorders. This study aimed to investigate the relationship between multivitamins and neurological and growth disorders.A cross-sectional study was conducted with 16921 subjects who visited the Children's Hospital of Nanjing Medical University from 2019 to 2021. The subjects were categorized into two groups based on their health status including 9368 cases (4484 with neurological disorders and 4884 with growth disorders) and 7553 healthy controls. Statistical tests including the T-test, Wilcoxon Rank Sum test, and Chi-Square test were employed to compare the groups, and logistic regression and Weighted Quantile Sum (WQS) regression were used to identify associations.In the adjusted logistic regression, serum 25 hydroxyvitamin D [25(OH)D], vitamin B2, and vitamin B9 were associated with decreasing risks of neurological disorders, whereas vitamin A, vitamin B1, and vitamin B12 were associated with increasing risks of neurological disorders. Nevertheless, vitamin A and vitamin B2 were associated with increasing risks of growth disorders. In the WQS model, nine multivitamins were positively associated with risks of neurological disorders, and Vitamins D and C were weighted the most. In addition, the inverse association but not statistically significant was observed between multivitamins and growth disorders, particularly growth retardation revealed a negative association, and some individual growth disorders revealed positive associations including obesity and malnutrition.In general, the study observed that multivitamins may be associated with neurological and growth disorders either positive or negative depending on the type of disorder.